Influence of Mass Concentration on Microstructure and Pore Structure of Coal-Gangue-Based Green Cemented Filling Body - Jisheng Qiu; Minmin Yang; Kun Cheng; Xiao Guan; Xi Luan; Zhijie Xiao (Journal of Engineering)
In response to China’s “double carbon” strategic goal, the problem of large emissions of coal gangue and low utilization rate of gangue cemented backfill with fly ash as admixture needs to be solved urgently. Based on this, this paper uses coal gangue powder as admixture and coal gangue as coarse and fine aggregate to prepare coal-gangue-based green cemented filling body (CGGCFB) with different mass concentrations (MC). The workability, mechanical properties, and microscopic pore structure (nuclear magnetic resonance and scanning electron microscope) were measured, respectively, to explore the effect of MC on the above mentioned properties. In terms of macroscopic properties, with the increase of MC from 80% to 82% and 84%, the slump of filling slurry decreased by 18.37% and 32.65%, the expansion decreased by 30% and 54.55%, and the bleeding rate decreased by 28.3% and 60.38%. The uniaxial compressive strength (UCS) of CGGCFB at different ages increased to varying degrees, and the maximum was 2.9 times of the original. In terms of microscopic pore structure characteristics, the total number of pores of CGGCFB decreases, the pore size changes from large to small, the shape tends to be uniform and circular, the force characteristics of the pores are improved, the complexity and tortuousness of the pore channels increase, and the inner surface of the pores becomes rough; the test results show that the performance of the backfill with a mass concentration of 82% is reasonable, and the utilization rate of coal gangue can be increased to 72%. The research results of this paper can further improve the utilization rate of coal gangue resources, and provide a theoretical reference for the research and application of coal gangue in mine filling.